Pre-operative Short Form Survey is Predictive of Return to Play and Minimal Clinically Important Difference after Anterior Cruciate Ligament Reconstruction. Issue 7 (21st July 2017) - Nwachukwu, Benedict U.; Chang, Brenda; Voleti, Pramod Babu; Berkanish, Patricia; Cohn, Matthew; Altchek, David W.; Allen, Answorth A.; Williams, Riley J.
Objectives: The purpose of this study was to investigate the role of pre-operative outcome scores for predicting minimal clinically important difference (MCID) and return to play (RTP) after anterior cruciate ligament reconstruction (ACLR). Methods: Patients enrolled as part of a prospective institutional ACL registry were eligible for this study. 294 active athletes with a minimum two-year follow-up were eligible for inclusion. A telephone-based questionnaire was administered to elicit factors associated with RTP. Patient reported outcome measures were captured as part of the registry at pre-operative, one-year and two-year follow-up. Outcome measures captured included: International Knee Documentation Committee (IKDC) Subjective Knee Evaluation, Lysholm scale, and SF-12 Physical and Mental component scales (PCS and MCS). Pre-operative outcome score thresholds predictive of RTP were determined using receiver operating characteristic (ROC) with area under the curve (AUC) analysis. MCID was calculated using a distribution-based method. Multivariable logistic models were fitted for achieving MCID and RTP while adjusting for age, sex and body mass index (BMI). Results: 231 patients at a mean follow-up of 3.7 years were included from 294 eligible patients. Mean age and BMI was 26.7 (SD+ 12.5) years and 23.7 (SD+ 3.1) respectively. Of the 231 patients, 201 returned to play (87.0%) at a mean time of 10.1 months. Mean pre-operative outcome scores on the IKDC, Lysholm, SF-12 PCS and SF-12 MCS were 50.1, 61.2, 41.5, and 53.6 respectively. Mean scores at two-year follow-up were 87.4, 89.5, 54.7 and 55.7 respectively. Corresponding MCID values were 9.0, 10.0, 5.1 and 4.3 on the IKDC, Lysholm, SF-12 PCS, and SF-12 MCS respectively. Pre-operative scores (AUC) most predictive of RTP were 60.9 (0.54), 57.0 (0.52), 42.3 (0.61) and 48.3 (0.63) however none of these score thresholds independently achieved significance. Pre-operative scores on each outcome tool were predictive of achieving MCID on that same tool across all outcome tools (p<0.0001 for all). Additionally pre-operative SF-12 MCS was predictive of MCID on the IKDC (OR 1.27, 1.11-1.52) and Lysholm (OR 1.08, 1.00-1.16). On the SF-12 MCS, medial meniscal injury was predictive for not achieving MCID (OR 0.19, 0.03-0.88) while non-white race was positively predictive (OR 3.83, 1.08-13.9). For RTP, higher pre-operative SF-12 PCS (OR 2.73, 1.09-7.62) and MCS (OR 4.41, 1.80-10.93) were predictive for achieving RTP and ACL allograft (OR 0.26, 0.06-1.00) was negatively predictive. No other outcome tool or variable reached significance. Conclusion: The rate of RTP after ACLR is high. Pre-operative outcome score on each tool is predictive of achieving a meaningful post-operative outcome score on that tool. Additionally, the SF-12 MCS is robustly predictive of achieving MCID across other outcome tools. Both pre-operative SF-12 MCS and PCS scores are independently predictive of RTP. We propose that the SF-12 is a highly useful post-ACL injury screening tool. These findings have implications for screening patients pre-operatively and counseling athletes on expected probabilities for RTP.